Education Policy, Theories, and Trends in the 21st Century International and Israeli Perspectives - Berkovich, Izhak; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book provides a highly accessible overview of public education policy. It organizes knowledge about 21st century education policy around two main topics: the policy process, and the discourse on public education policy. This unique organization provides a novel lens for better understanding the dynamics and contents of current education policy making. The work also offers a broad overview of theories of public policy, economics, demography, sociology, history, and psychology. Each chapter includes a discussion of data derived from the international and Israeli contexts. The book provides a series of valuable insights relevant to researchers, practitioners, and policymakers interested in understanding the multifaceted aspects that shape contemporary education policy. .
Preface -- 1. Introduction to Education Policy -- 1.1 Definitions and basic concepts -- 1.2 Public education in the 21st century -- 1.3 Values and ideologies in education -- 1.4 Summary of the chapter -- References -- 2. The Policy Process: The Design of Education Policy -- 2.1 Power, politics, and agenda setting -- 2.2 Key players and the social construction of the target population -- 2.3 Decision-making processes and ethical aspects of decision making -- 2.4 Summary of the chapter -- References -- 3. The Policy Process: Implementation of Education Policy -- 3.1 Policy instruments -- 3.2 Field effects on implementation -- 3.3 Evaluation of education policy -- 3.4 System change and education reform -- 3.5 Summary of the chapter -- References -- 4. The Policy Process: Contextual Factors -- 4.1 Demographic and economic aspects -- 4.2 Political culture -- 4.3 National culture and social cohesion -- 4.4 Summary of the chapter -- References -- 5. Contemporary Discourse in Education Policy in the 21st Century: Problems -- 5.1 Public education in crisis -- 5.2 Bureaucratic structure and central government -- 5.3 Poor professionalization in teaching -- 5.4 Inequality in education -- 5.5 Summary of the chapter -- References -- 6. Contemporary Discourse in Education Policy in the 21st Century: Solutions -- 6.1 Promoting school effectiveness -- 6.2 Promoting teaching as a profession -- 6.3 Promoting equality in education -- 6.4 Summary of the chapter -- References -- 7. Criticism of education policy as a field of knowledge -- 7.1 Criticism of the basic assumptions and conceptualization of studies in education policy -- 7.2 Criticism of comparative studies in education policy -- 7.3 Criticism of evaluation studies in education policy -- 7.4 Summary of the chapter -- References. .
Keywords: Education and state; Educational sociology; School management and organization; School administration; Educational Policy and Politics; Sociology of Education; Education Policy; Organization and Leadership